2017
DOI: 10.1515/jppr-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effect of botanical insecticide, palizin in comparison with chemical insecticide, imidacloprid on the black citrus aphid, Toxoptera aurantii Boyer de Fonscolombe and its natural enemy, Aphidius colemani Viereck

Abstract: Th e black citrus aphid, Toxoptera aurantii Boyer de Fonscolombe (Hemiptera: Aphididae), an important pest of citrus species, feeds by sucking sap from plant leaves. It causes some leaf distortion and malformation of growing leaves and shoot tips. In this study, the eff ects of the botanical insecticide, palizin on T. aurantii and its parasitoid, Aphidius colemani Viereck (Hymenoptera: Brachonidae) were compared with the chemical insecticide, imidacloprid. Th e compounds were evaluated at maximum recommended f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, functional studies of the new insecticide targets in aphids were also conducted in these aphids (Ye et al, 2019 ; Shang et al, 2020a ). However, most previously published papers have focused on the ecology (Alizadeh Kafeshani et al, 2018 ; Guidolin and Consoli, 2018 ; Li et al, 2019 ), control (Aslam et al, 2015 ; Gholamzadeh-Chitgar and Pourmoradi, 2017 ), and mitochondrial genome (Wang et al, 2019 ) in tea aphid Ap. aurantii .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, functional studies of the new insecticide targets in aphids were also conducted in these aphids (Ye et al, 2019 ; Shang et al, 2020a ). However, most previously published papers have focused on the ecology (Alizadeh Kafeshani et al, 2018 ; Guidolin and Consoli, 2018 ; Li et al, 2019 ), control (Aslam et al, 2015 ; Gholamzadeh-Chitgar and Pourmoradi, 2017 ), and mitochondrial genome (Wang et al, 2019 ) in tea aphid Ap. aurantii .…”
Section: Introductionmentioning
confidence: 99%
“…Active compounds of this botanical insecticide were less toxic to mammalian and would be naturally degraded in specific periods, thus safer to human health and the environment (El-Wakeil, 2013). Several reports also indicated that botanical insecticides had high specificity on targeted insect pests (Gholamzadeh-Chitgar & Pourmoradi, 2017;Zeb, Naeem, Khan, & Ahmad, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptomes of an increasing number of species have been deposited and accessible in public databases, such as the National Center of Biotechnology Information (NCBI) Sequence Read Archive (SRA) database, which is the most popular repository of RNA-Seq data. No such data for A. aurantii is available in that database, as the majority of the published studies have focused on its ecology or control ( Aslam et al, 2015 ; Zekri et al, 2016 ; Gholamzadeh-Chitgar and Pourmoradi, 2017 ; Alizadeh Kafeshani et al, 2018 ; Li L. et al, 2019 ). In addition to protein-coding genes, non-coding genes also play important roles in insects, e.g., long non-coding RNAs (lncRNAs), defined as transcripts longer than 200 nucleotides that do not show any protein-coding capability ( Legeai and Derrien, 2015 ).…”
Section: Introductionmentioning
confidence: 99%